Adiponectin levels predict prediabetes risk: the Pathobiology of Prediabetes in A Biracial Cohort (POP-ABC) study. Issue 1 (17th March 2016) - Jiang, Yunna; Owei, Ibiye; Wan, Jim; Ebenibo, Sotonte; Dagogo-Jack, Samuel
Abstract : Background: Adiponectin levels display ethnic disparities, and are inversely associated with the risk of type 2 diabetes (T2DM). However, the association of adiponectin with prediabetes risk in diverse populations has not been well-studied. Here, we assessed baseline adiponectin levels in relation to incident prediabetes in a longitudinal biracial cohort. Research design and methods: The Pathobiology of Prediabetes in A Biracial Cohort study followed non-diabetic offspring of parents with T2DM for the occurrence of prediabetes, defined as impaired fasting glucose and/or impaired glucose tolerance. Assessments at enrollment and during follow-up included a 75 g oral glucose tolerance test, anthropometry, biochemistries (including fasting insulin and adiponectin levels), insulin sensitivity and insulin secretion. Logistic regression was used to evaluate the contribution of adiponectin to risk of progression to prediabetes. Results: Among the 333 study participants (mean (SD) age 44.2 (10.6) year), 151(45.3%) were white and 182 (54.8%) were black. During approximately 5.5 (mean 2.62) years of follow-up, 110 participants (33%) progressed to prediabetes (N=100) or T2DM (N=10), and 223 participants (67%) were non-progressors. The mean cohort adiponectin level was 9.41+ 5.30 μg/mL (range 3.1–45.8 μg/mL); values were higher in women than men (10.3+ 5.67 μg/mL vs 7.27+ 3.41 μg/mL, p<0.0001) and in white than black offspring (10.7+ 5.44 μg/mL vs 8.34+ 4.95 μg/mL, p<0.0001). Adiponectin levels correlated inversely with adiposity and glycemia, and positively with insulin sensitivity and high-density lipoprotein cholesterol levels. Baseline adiponectin strongly predicted incident prediabetes: the HR for prediabetes per 1 SD (approximately 5 μg/mL) higher baseline adiponectin was 0.48 (95% CI 0.27 to 0.86, p=0.013). Conclusions: Among healthy white and black adults with parental history of T2DM, adiponectin level is a powerful risk marker of incident prediabetes. Thus, the well-known association of adiponectin with diabetes risk is evident at a much earlier stage in pathogenesis, during transition from normoglycemia to prediabetes.